An inverse method for optimization of geometric parameters of a Savonius-style wind turbine - Roy, Sukanta; Das, R.; Saha, U. (Elsevier, 2018)
© 2017 Elsevier Ltd This work is aimed at optimizing the dimensions of a semicircular-bladed Savonius Style Wind Turbine (SSWT) using Differential Evolution (DE) based inverse optimization methodology to simultaneously satisfy a given power and torque characteristics. The results obtained from the inverse analysis are well-validated with the experimental wind tunnel results available under different wind speeds. The effect of necessary blockage corrections is considered. Using DE-assisted inverse method, the present study demonstrated smaller turbine dimensions than those reported in various literature and also yields a lower value of the blockage ratio. The overall area of the SSWT is found to be reduced upto 9.8% with respect to the corresponding experimental wind tunnel data. The improvement is attributed due to an optimized interplay between multiple combinations of parameters satisfying a given power and torque. To achieve a given power and torque requirement under a given range of tip speed ratio, it appears from the study that the blade overlap can be significantly regulated through minor adjustments of the chord length and turbine height. The sensitivity analysis reveals that the aspect ratio governing parameters such as turbine height and chord length are critical factors governing the torque and power output from SSWTs. In order to meet a desired power and torque, the present study offers a novel inverse methodology aided by the DE algorithm to simultaneously estimate and optimize geometric parameters of SSWT. The benefit of this work is to provide an alternative and optimized solution to the existing literature data where the overall area of SSWT can be reduced and significant material along with space savings can be accomplished.